Inicjatywa założenia ochron dla dzieci w Krakowie w pierwszej połowie XIX wieku - Barnaś-Baran, Ewa (Biuletyn Historii Wychowania, 2017)
The article covers the issue of the initiative of organising care for small children at care homes in Krakow in the first half of the 19th century. Krakow’s civic-minded townspeople, referring to examples from all over Europe and facilities organised in Warsaw, implemented a project setting up a care shelter in Krakow. The analysis of archive material indicates that towards the end of the 1830s and the beginning of the 1840s, in Krakow, one could speak of the beginnings of a movement aimed at extending care over children of working families, including helping to feed them, morally educate them and provide for them with a basic education. Members of Krakow’s Charity Society actively participated in this work, recruiting people interested in creating care shelters, and drawing up projects for such institutions. In the end, care shelters were established and operated in the second half of the 19th century on the initiative of the private individuals who founded the Committee for Shelters for small children in Krakow. It must be noted that these included members of the Charity Society.